2016 Thunderstorm-asthma epidemic in Melbourne, Australia: An analysis of patient characteristics associated with hospitalization - Harun, N; Lachapelle, P; Bowatte, G; Lodge, C; Braitberg, G; Irving, L; Hinks, T; Dharmage, S; Douglass, J (Taylor and Francis, 2020)
Rationale: On November 21, 2016 in Australia, a major thunderstorm-asthma epidemic struck Melbourne with an unprecedented number of emergency presentations, hospital admissions and fatalities.